2020
DOI: 10.3389/fneur.2020.00185
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Augmented Reality Visual Cues on Turning in Place in Parkinson's Disease Patients With Freezing of Gait

Abstract: Background: Turning in place is particularly bothersome for patients with Parkinson's disease (PD) experiencing freezing of gait (FOG). Cues designed to enforce goal-directed turning are not yet available. Objectives: Assess whether augmented reality (AR) visual cues improve FOG and turning in place in PD patients with FOG. Methods: Sixteen PD patients with FOG performed a series of 180 • turns under an experimental condition with AR visual cues displayed through a HoloLens and two control conditions (one cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 27 publications
0
35
0
1
Order By: Relevance
“…Participants indeed stated that they had trouble with stepping onto or over cues (see Supplementary Material 2 ), for which unnatural head postures were required to see the nearby holographic cues during the targeted step or crossing maneuver. As such, the small mixed-reality field of view thus limited the action relevance of holographic cues and their immediate effect on FOG, which could also have played a role in previous studies showing null effects with related technology and cueing applications ( 19 , 27 , 30 , 31 ). Interestingly, mixed-reality field of view and wearer comfort have allegedly already strongly improved with the latest generation of mixed-reality headsets, such as HoloLens 2 and Magic Leap 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants indeed stated that they had trouble with stepping onto or over cues (see Supplementary Material 2 ), for which unnatural head postures were required to see the nearby holographic cues during the targeted step or crossing maneuver. As such, the small mixed-reality field of view thus limited the action relevance of holographic cues and their immediate effect on FOG, which could also have played a role in previous studies showing null effects with related technology and cueing applications ( 19 , 27 , 30 , 31 ). Interestingly, mixed-reality field of view and wearer comfort have allegedly already strongly improved with the latest generation of mixed-reality headsets, such as HoloLens 2 and Magic Leap 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in controlled lab environments examining the effect of holographic visual cues on FOG showed no demonstrable effect during walking (19,30) or turning (31), which may be attributable to the overall low occurrence of FOG observed in the lab (30). Another limitation in previous research on wearable cueing devices is the absence of a control condition without the wearable (19,30,31), leaving the influence of potential unfamiliarity effects of the wearable (e.g., distraction) on FOG unexplored. Mixed-reality headsets are currently quite heavy (e.g., HoloLens 1 weighs 579 g) and uncomfortable (19) and can therefore divert attention.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Palacios-Navarro et al [ 38 ] aimed to determine the effects of an AR-based mole stomping game on the gait function of Parkinson patients, and they also found that the 30-minute game with 4 sessions per week for 5 weeks is effective to improve the completion time score and walk function. However, some conflicting and equivocal results have been proposed by Janssen et al [ 39 ]. In their study, the acute effects of AR-based visual cues on freezing of gait and turning in place of Parkinson patients were assessed, and the results showed that the AR-based visual cues did not reduce freezing of gait and even worsen some gait kinematics and turning in place.…”
Section: Resultsmentioning
confidence: 99%
“…The HL system has been examined as a rehabilitation tool in the clinical arena and utilized to provide digital content to individuals with PD, with the aim of improving spatio-temporal measures of gait, turning, and improvements in balance stability [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%